2008
DOI: 10.1039/b808930b
|View full text |Cite
|
Sign up to set email alerts
|

Cross-metathesis of oleyl alcohol with methyl acrylate: optimization of reaction conditions and comparison of their environmental impact

Abstract: The synthesis of a,w-difunctional monomers from the renewable resource oleyl alcohol via a cross-metathesis reaction with methyl acrylate is described. The reaction conditions were optimized for high conversions in combination with high cross-metathesis selectivity. The introduction of a protecting group for the alcohol functionality of oleyl alcohol was found to be a necessary step in order to significantly reduce the amount of metathesis catalyst required to obtain full conversions and good selectivities. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 22 publications
1
44
0
2
Order By: Relevance
“…Catalyst IV was also the most efficient for the reaction of 8 ([8] = 0.1 M) with 4 equivalents of acrylonitrile in toluene at 100°C for 1 h. With 5 mol% of catalyst the nitrile ester 12 was obtained (86%) as a mixture of Z (major) and E isomers (2.9/1) with a small amount of C10 ester with a terminal double bond [52]. Thus the cross-metathesis with acrylonitrile of alkenes containing an internal double bond can be efficiently achieved, as it was also possible with acrylic esters [16,17]. Using syringe pump addition of catalyst IV at 100°C for 5 h, the unsaturated nitrile ester 10 was obtained in 88% yield, with high TON of 1960 [53].…”
Section: Cross-metathesis Of Unsaturated Esters With Acrylonitrilementioning
confidence: 90%
See 2 more Smart Citations
“…Catalyst IV was also the most efficient for the reaction of 8 ([8] = 0.1 M) with 4 equivalents of acrylonitrile in toluene at 100°C for 1 h. With 5 mol% of catalyst the nitrile ester 12 was obtained (86%) as a mixture of Z (major) and E isomers (2.9/1) with a small amount of C10 ester with a terminal double bond [52]. Thus the cross-metathesis with acrylonitrile of alkenes containing an internal double bond can be efficiently achieved, as it was also possible with acrylic esters [16,17]. Using syringe pump addition of catalyst IV at 100°C for 5 h, the unsaturated nitrile ester 10 was obtained in 88% yield, with high TON of 1960 [53].…”
Section: Cross-metathesis Of Unsaturated Esters With Acrylonitrilementioning
confidence: 90%
“…In some examples it was shown that acrylonitrile inhibits the ruthenium-catalysed cross-metathesis of functional alkenes, whereas methyl acrylate does not inhibit this reaction as some cross-metathesis can be performed in bulk in methyl acrylate [16,17,[70][71][72]. Thus, it appeared that the linear amino ester 18 could also arise from the cross-metathesis of the 10-undecenenitrile 21 with methyl acrylate followed by hydrogenation.…”
Section: Cross-metathesis Of Renewable 10-undecenenitrile and Methyl mentioning
confidence: 99%
See 1 more Smart Citation
“…[121] Auch die KM von Fettalkoholen wurde untersucht. Dabei wurden ungewollte Nebenreaktionen, geringe Umsätze sowie schlechte Selektivität beobachtet, [122] wahrscheinlich weil Alkohole Ruthenium-Metathesekatalysatoren zersetzen können. [123] Um dies zu umgehen, wurden die gewünschten w-Hydroxyfettsäureester mittels KM von acetatgeschützten Fettalkoholen mit Methylacrylat in einer effizienten katalytischen Reaktion hergestellt.…”
Section: üBergangsmetallkatalysierte Additionenunclassified
“…[123] Um dies zu umgehen, wurden die gewünschten w-Hydroxyfettsäureester mittels KM von acetatgeschützten Fettalkoholen mit Methylacrylat in einer effizienten katalytischen Reaktion hergestellt. [122] Im Gegensatz hierzu war die Schutzgruppenstrategie bei der KM von 5 b nicht erforderlich (Schema 15), was darauf hindeutet, dass sekundäre Alkohole von den unterSchema 11. Hydroaminomethylierung von 1 c mit Morpholin.…”
Section: üBergangsmetallkatalysierte Additionenunclassified